Integrating Foundational Skills and Student-Centered Literacy: Insights from Self-Determination Theory - Savannah S Maydew (The Advocate, 2025)
Teacher–student relationships play a pivotal role in fostering student motivation, engagement, and achievement, yet debates about literacy instruction often overlook how curricular choices shape these relationships. This article examines how Self-Determination Theory (SDT) can serve as a fulcrum for integrating explicit foundational skills instruction with student-centered literacy experiences in ways that support autonomy, competence, and relatedness. Drawing on Progressive, Constructivist, Humanistic, and Social Learning traditions, the paper situates SDT within the historical context of the “Reading Wars” and current policy shifts tied to the Science of Reading. The HEART Model for Teacher-Student Relationships—Holistic, Enthusiastic, Approachable, Responsive, and Transformative—is introduced as a framework that operationalizes SDT through relational pedagogy. Implications highlight how teacher preparation programs can equip candidates to balance rigor with responsiveness, ensuring literacy instruction that advances achievement while sustaining student motivation.
Keywords: Self-Determination Theory (SDT); teacher-student relationships (TSR); curriculum theory; Science of Reading; student motivation